Haploinsufficiency of POU4F1 causes an ataxia syndrome with hypotonia and intention tremor. Issue 6 (15th April 2021) - Webb, Bryn D.; Evans, Anthony; Naidich, Thomas P.; Bird, Lynne M.; Parikh, Sumit; Fernandez Garcia, Meilin; Henderson, Lindsay B.; Millan, Francisca; Si, Yue; Brennand, Kristen J.; Hung, Peter; Rucker, Janet C.; et al.
Abstract: De novo, heterozygous, loss‐of‐function variants were identified in Pou domain, class 4, transcription factor 1 ( POU4F1 ) via whole‐exome sequencing in four independent probands presenting with ataxia, intention tremor, and hypotonia. POU4F1 is expressed in the developing nervous system, and mice homozygous for null alleles of Pou4f1 exhibit uncoordinated movements with newborns being unable to successfully right themselves to feed. Head magnetic resonance imaging of the four probands was reviewed and multiple abnormalities were noted, including significant cerebellar vermian atrophy and hypertrophic olivary degeneration in one proband. Transcriptional activation of the POU4F1 p.Gln306Arg protein was noted to be decreased when compared with wild type. These findings suggest that heterozygous, loss‐of‐function variants in POU4F1 are causative of a novel ataxia syndrome. Abstract : Heterozygous, loss of function variants in POU4F1 cause a novel ataxia syndrome.